Fungsi Legislasi Dewan Perwakilan Daerah dalam Pembentukan Undang-Undang - Yabes Abraham Hau Wele; Yosef Mario Monteiro; Rafael Rape Tupen (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Legislation function owned by DPD is still limited, it shows the weak position and role (position and function) of DPD when compared with DPR. DPD does not have the authority to form laws together with DPR and the President and has no authority in setting the state budget. The formulation of the problem in this study are: (1) How is the legislative function of the House of Regional Representatives in the formation of the Act? (2) What is the ratio of the legislative function of the House of Regional Representatives that is different from the House of Representatives? This research is a normative juridical research which can be interpreted as a library legal research conducted based on literature or secondary data. In other words, this research is library research (library reseach), meaning that this research is conducted by reading works related to the issues to be studied and then containing a study of the research. The results of research and discussion show that: (1) The legislative function of DPD has a major role in the formation of the Act at the stage of discussion and ratification. At the discussion stage, although its participation is limited to level 1, DPD provides input and consideration of the bill relating to regional autonomy, central-regional relations, and management of economic and natural resources. Furthermore, at the stage of ratification, a joint agreement between DPR and the President strengthens the status of the bill into law. Although DPD can provide input and consideration of some bills, the final decision remains in the hands of DPR. This confirms that the main role of DPD is more as an advisory body in the legislative process. DPR has greater power than DPD in the formation of the Act, with the authority to take the final decision. Thus, although DPD has an important role in certain aspects of the formation of the Act, the main power and final decision remains with DPR. (2) Comparison of legis ratio between DPD and DPR has different representation. DPD represents the interests of the region directly, while DPR represents the interests of the people through political parties. DPD is present to accommodate regional aspirations that are not always represented by DPR. This reflects that the legislative role of DPD has significant limitations. DPD should function as a mechanism of checks and balances in Indonesia's bicameral system. However, due to its limited authority, the implementation of this function has not been optimally realized. Thus, although DPD has an important role in representing regional aspirations, the differences in authority and rights between DPD and DPR cause their position to be unbalanced in the legislative process.